Factors affecting dislocation after bipolar hemiarthroplasty in patients with femoral neck fracture. Issue 3 (March 2020) - Kizkapan, Turan Bilge; Misir, Abdulhamit; Uzun, Erdal; Oguzkaya, Sinan; Ozcamdalli, Mustafa
Highlights: Patients with dislocation become susceptible to various complications and morbidities. Clinicians should pay attention to prevent hip dislocation after HA. Smaller OP, CE angle of the operated side, and higher FHEI and smaller HHC of the non-operated side should be monitored. These factors are associated with a high incidence of dislocation. Abstract: Purpose: This study aimed to investigate the anatomic risk factors associated with dislocation following bipolar hemiarthroplasty for the treatment of femoral neck fracture. Materials and Methods: We retrospectively reviewed 208 consecutive patients (133 women, 75 men) with femoral neck fractures who were treated with bipolar hemiarthroplasty between 2015 and 2018. A comparative analysis was performed between dislocation ( n  = 18) and non-dislocation ( n  = 190) groups in terms of patient demographics, surgical and pelvic morphologic factors, and clinical outcomes, including postoperative Harris and modified Harris hip scores. Independent risk factors affecting dislocation were also evaluated. Results: The mean follow-up period was 30.8 ± 2.0 (range, 12–48) months. The mean age was 79.2 ± 7.4 (range, 71–94) years. The dislocation rate was 8.6% (18/208), and the mean dislocation time after operation was 2.0 ± 1.1 (range, 1–4) months. Patient-related factors did not differ between the dislocated and non-dislocated groups. As regards dislocation, statistically significant difference was observed in surgical and pelvic morphologic factors, including femoral offset, residual femoral neck length, trochanter upper end and femoral head center distance, and height of the hip center of the operated side ( p  = 0.025, p  = 0.013, p  = 0.002, p  = 0.008, respectively). Moreover, the femoral offset, height of the hip center, and femoral neck-shaft angle of the non-operated side are significantly different between the groups ( p  = 0.007, p  = 0.001, p  = 0.027, respectively). Decrease in the center edge (CE) angle, offset of prosthesis, and increase in femoral head extrusion index (FHEI) of the operated side and decrease in the height of the hip center of the non-operated side increased the risk of dislocation ( p  = 0.030, OR: 1, 306; p  = 0.041, OR: 8.15; p  = 0.020, OR: 1.038; p  = 0.010, OR: 2.02, respectively). Conclusions: Pelvic morphologic features and surgical factors were found to affect dislocation. Patients with smaller OP, CE angle of the operated side, and higher FHEI and smaller height of the hip center of the non-operated side should be carefully monitored to decrease postoperative dislocation.